A polymorphism in the TYMP gene is associated with the outcome of HLA‐identical sibling allogeneic stem cell transplantation. Issue 10 (1st August 2013) - Guillem, Vicent; Hernández‐Boluda, Juan Carlos; Gallardo, David; Buño, Ismael; Bosch, Anna; Martínez‐Laperche, Carolina; de la, Rafael; Brunet, Salut; Martin, Carmen; Nieto, José B.; Martínez, Carmen; Pérez, Ariadna; et al.
<x xml:space="preserve">Abstract</x> Thymidine phosphorylase (TYMP), an enzyme involved in nucleotide synthesis, has been implicated in critical biological processes such as DNA replication, protection against mutations, and tissue repair. In this work, we retrospectively evaluated the influence of a polymorphism in the TYMP gene (rs112723255; G/A) upon the outcome of 448 patients subjected to allogeneic stem cell transplantation (allo‐SCT) from an human leukocyte antigen (HLA)‐identical sibling donor. The TYMP genotype of patients correlated with overall survival—carriers of the minor allele (A) being at an increased risk of dying after transplantation (hazard ratio, HR = 1.9; P = 0.004). This effect was mostly due to differences in transplant toxicity‐related mortality (HR = 2.5; P = 0.029). In addition, the TYMP genotype of donors was associated with the risk of chronic graft‐versus‐host disease (GVHD)—carriers of the minor allele being at an increased risk of developing this complication ([HR] = 1.7; P = 0.039). The impact of such polymorphism on the risk of chronic GVHD is limited to patients transplanted in early stage disease (HR = 2.2; P = 0.019). The combination of a donor harboring the minor allele with a patient homozygous for the major allele was associated with the highest risk of chronic GVHD (HR = 2.8; P = 0.008). These findings provide the first evidence of the significant impact of the TYMP genotype upon the clinical outcome of patients treated with HLA‐identical sibling allo‐SCT. Am. J. Hematol. 88:883–889, 2013. © 2013 Wiley Periodicals, Inc.